Penerapan Identiti Senibina Ke Atas Bangunan Tinggi : Kajian Kes Urban Hive Dan Lotte World Tower, Seoul, Korea Selatan - Moey Sui Min; Mastor Surat; Noor Hayati Ismail (Department of Architecture of Universiti Kebangsaan Malaysia (UKM) and The Association of Malaysian Malay Architects Entrepreneurs (ARKIM), 2024)
Non-Indexed Publication